General characteristics of the claim in the countries of the anglo-saxon and continental law - Волкова, Наталія Василівна; Волкова, Н. В.; Волкова, Наталия Васильевна; Volkova, Nataliia V.; Притуляк, Валерій Миколайович; Притуляк, В. М.; Притуляк, Валерий Николаевич; Prytuliak, Valerii M.; Цал-Цалко, Юлія Юліївна; Цал-Цалко, Ю. Ю.; Цал-Цалко, Юлия Юлиевна; Tsal-Tsalko, Yuliia Yu.; et al. (Editorial Primmate S. A. S., 2019)
The relevance of the article is to investigate the concept of lawsuits and class actions in the leading countries of the world. The object of the study is the public relations that arise when civil actions are brought in court. The subject of the study is the law of foreign countries, which define the civil lawsuit, its legal nature. In accordance with the goals and objectives set, the basis of the methodology of the study were general scientific and special methods of knowledge of legal phenomena. The authors analyzed the legal acts of the USA, Germany, the United Kingdom, the Netherlands, Sweden, France, and the Netherlands. Based on the research, the authors made conclusions about the legal nature of the lawsuit, defining the concept of the lawsuit in the acts of normative-legal acts of foreign countries. The conclusion about the status of the class-action lawsuit in foreign countries and the further improvement of the domestic class-action lawsuit was also made.

Актуальність статті полягає в дослідженні поняття позову та групових позовів в провідних країнах світу. Об'єктом дослідження є суспільні відносини, які виникають при подачі цивільних позовів до суду. Предметом дослідження є норми законодавства зарубіжних країн, яка надають визначення цивільном позову, його правовій природі. Відповідно до поставлених мети і задач основою методології дослідження стали загальнонаукові та спеціальні методи пізнання правових явищ. Авторами проаналізовані нормативно-правові акти США, Німеччини, Великобританії, Нідерландів, Швеції, Франції та Нідерландів. На основі дослідження авторами були зроблені висновки щодо правової природи позову, визначення поняття позову в актах нормативно-правових актах зарубіжних країн. Також зроблено висновок про стан інституту групових позовів зарубіжних країнах та про подальше удосконаленні вітчизняного інституту групових позовів.
Volkova N. General characteristics of the claim in the countries of the anglo-saxon and continental law / N. Volkova, V. Prytuliak, Yu. Tsal-Tsalko, I. Yanitska, Yu. Poliuk // Amazonia Investiga. – Vol. 8. – Iss. 22. – Editorial Primmate S. A. S., 2019. – P. 350-356.
Keywords: civil lawsuit; concept of the lawsuit; nature of the lawsuit; class-action lawsuit; цивільний позов; поняття позову; природа позову; групові позови; Research Subject Categories::LAW/JURISPRUDENCE